Air tightness detection device for solid oxide battery
Through the airtightness detection device of solid oxide batteries, the airtightness of the seal is detected by using ceramic oxygen pumps and potential polarization method, which solves the problems of low detection accuracy and high cost in the prior art, and achieves high efficiency and accuracy airtightness detection.
Patent Information
- Application Number
- CN202411031089.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-07-30
AI Technical Summary
The prior art is difficult to effectively detect the airtightness of solid oxide battery seals, resulting in high detection cost, low accuracy and poor reliability.
The airtightness detection device of a solid oxide battery is adopted, which includes a ceramic oxygen pump, a second electrolyte layer and a seal. The airtightness of the seal is detected by a constant potential polarization method, and the steady-state current displayed by an ammeter is used. The value reflects the gas leakage rate of the seal.
It realizes high-precision detection of the airtightness of solid oxide battery seals, which is low in cost and easy to operate, and can quantitatively characterize leakage rates at different temperatures and pressures, meeting the US Department of Energy's SECA program's sealing material leakage standard.
Smart Images

Figure CN119437575A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide batteries, and in particular to an air tightness detection device for solid oxide batteries. Background Art
[0002] Solid oxide battery (SOC) is an all-solid-state energy conversion device based on ceramic electrolyte membrane. Through high-temperature sealing of seals, single cells are connected in series with current collectors, connectors and other components to form a battery stack. The airtightness of seals is one of the bottlenecks restricting the development of solid oxide batteries. At present, physical methods such as pressure difference method and pressure drop method are generally used to detect the airtightness of seals. These methods require the construction of complex detection devices, and it is not easy to ensure the uniformity of pressure and the accuracy of results. Generally, multiple experiments are required to reduce errors. Summary of the invention
[0003] The purpose of the present invention is to provide a solid oxide battery airtightness detection device, which can quantitatively characterize the sealing airtightness of the sealing member in situ, has low detection cost, high precision and high reliability.
[0004] To achieve the above object, the technical solution adopted by the present invention is: a gas tightness detection device for a solid oxide battery, comprising: a ceramic oxygen pump located at the top, a second electrolyte layer located at the bottom, and a seal located between the ceramic oxygen pump and the second electrolyte layer, the ceramic oxygen pump is composed of a first porous electrode, a first electrolyte layer, and a second porous electrode stacked in sequence, the seal and the first electrolyte layer and the second electrolyte layer are surrounded to form a chamber, and the second porous electrode is located in the chamber; The first electrolyte layer and the second electrolyte layer are both ceramic materials with oxygen ion conductivity, the first porous electrode and the second porous electrode are electronically conductive materials or oxygen ion-electron mixed conductive materials, and the oxygen ion-electron mixed conductive materials are La 0.8 Sr 0.2 MnO 3-d ; The thickness of the first electrolyte layer and the second electrolyte layer is 10-1000 microns, the thickness of the first porous electrode and the second porous electrode is 10-1000 microns, the height of the chamber is 50-2000 microns, and the thickness of the sealing member is 50-2000 microns; It also includes: a constant voltage source and an ammeter, wherein the positive electrode of the constant voltage source is connected to the positive electrode of the ammeter, the negative electrode of the ammeter is connected to the first porous electrode of the ceramic oxygen pump through a metal wire, the negative electrode of the constant voltage source is connected to the second porous electrode of the ceramic oxygen pump through a metal wire, and the first porous electrode, the first electrolyte layer, the second porous electrode, the constant voltage source, and the ammeter form a loop.
[0005] The further improved scheme in the above technical scheme is as follows: 1. In the above scheme, the ceramic material with oxygen ion conductivity is yttria-stabilized zirconia, scandium-stabilized zirconia, samarium-doped cerium oxide, gadolinium-doped cerium oxide, strontium-magnesium co-doped gallium-lanthanum, erbium-stabilized bismuth oxide, doped barium zirconate or doped barium ceria, wherein 0 <x<1,0<y<1,0<δ<1。
[0006] 2. In the above solution, the thickness of the first electrolyte layer and the second electrolyte layer is 20 to 600 microns.
[0007] 3. In the above solution, the thickness of the first porous electrode and the second porous electrode is 20-500 microns.
[0008] 4. In the above solution, the height of the chamber is 200~1000 microns.
[0009] 5. In the above solution, the thickness of the sealing member is 200-1000 microns.
[0010] 6. In the above solution, the thickness of the sealing member is 200-1000 microns.
[0011] 7. In the above solution, the metal wire is a silver wire or a platinum wire.
[0012] 8. In the above scheme, the output voltage of the constant voltage source is 0.1~0.3 V.
[0013] 9. In the above scheme, the ceramic oxygen pump operates at 500~850℃.
[0014] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art: 1. The gas-tightness detection device of the solid oxide battery of the present invention has a steady-state current value displayed by its ammeter that directly reflects the gas leakage rate of the seal. The lower the steady-state current value, the higher the gas-tightness of the seal. Through the constant potential polarization method, this device can accurately detect the gas-tightness of the solid oxide battery stack seal in situ, and has the advantages of low cost and easy operation.
[0015] 2. The airtightness detection device of the solid oxide battery of the present invention is sealed with a glass seal by an electrochemical oxygen pump battery, and the oxygen reduction reaction occurring on the electrode of the oxygen pump battery at high temperature is used to pump out the oxygen in the sealed chamber and the oxygen leaked into the sealed chamber from the outside to reach the reaction kinetic equilibrium state, and the steady-state current generated by the reaction is monitored by an electrochemical workstation, and the magnitude of this steady-state current reflects the degree of leakage of the seal. The leakage value can be calculated by combining Faraday's law of electrolysis and the current magnitude detected by the electrochemical workstation. Using this method and device, quantitative characterization of the leakage rate of solid oxide batteries at different temperatures and pressures can be achieved. For example, under the condition of a high temperature of 800°C and a loading pressure of 0.23kPa, the airtightness test results of the ceramic oxygen pump device encapsulated with a seal are as follows: the current platform of the constant potential polarization is extremely low, the steady-state current magnitude is only 50nA, and the current magnitude is in the nanoampere level. Based on Faraday's law of electrolysis and the electrode reaction equation, it can be calculated that the leakage corresponding to the current is 2.6×10 -7 ml 3 ·min -1 cm -1 , which is lower than the standard value of 0.04 ml for sealing material leakage specified by the US Department of Energy SECA program 3 ·min -1 cm -1 , indicating that the seal 200 has excellent sealing ability under the temperature and pressure. And the time to reach the oxygen pump current platform is short, showing fast and efficient detection ability. Therefore, based on this method, the sealing of the solid oxide battery during operation can be quantitatively detected. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Attached Figure 1 It is a schematic structural diagram of the air tightness detection device of the solid oxide battery of the present invention; Attached Figure 2 The sealing leakage current curve of the glass seal of the present invention at 800°C, 0 and 0.23 KPa.
[0017] In the above figures: 1. Ceramic oxygen pump; 2. Second electrolyte layer; 3. Seal; 4. First porous electrode; 5. Second porous electrode; 6. First electrolyte layer; 7. Chamber; 8. Constant voltage source; 9. Ammeter. DETAILED DESCRIPTION
[0018] The present invention can be further understood through the specific embodiments given below, but they are not intended to limit the present invention.
[0019] Embodiment 1: A gas tightness detection device for a solid oxide battery, comprising: a ceramic oxygen pump 1 located at the top, a second electrolyte layer 2 located at the bottom, and a seal 3 located between the ceramic oxygen pump 1 and the second electrolyte layer 2, wherein the ceramic oxygen pump 1 is composed of a first porous electrode 4, a first electrolyte layer 6, and a second porous electrode 5 stacked in sequence, wherein the seal 3, the first electrolyte layer 6, and the second electrolyte layer 2 are surrounded to form a chamber 7, and the second porous electrode 5 is located in the chamber 7; The first electrolyte layer 6 and the second electrolyte layer 2 are both ceramic materials with oxygen ion conductivity, the first porous electrode 4 and the second porous electrode 5 are electronically conductive materials or oxygen ion-electron mixed conductive materials, and the oxygen ion-electron mixed conductive materials are La 0.8 Sr 0.2 MnO 3-d , which is more conducive to the occurrence of oxygen reduction process on the oxygen pump electrode; The thickness of the first electrolyte layer 6 and the second electrolyte layer 2 is 10-1000 microns, the thickness of the first porous electrode 4 and the second porous electrode 5 is 10-1000 microns, the height of the chamber 7 is 50-2000 microns, and the thickness of the sealing member 3 is 50-2000 microns; It also includes: a constant voltage source 8 and an ammeter 9, wherein the positive electrode of the constant voltage source 8 is connected to the positive electrode of the ammeter 9, the negative electrode of the ammeter 9 is connected to the first porous electrode 4 of the ceramic oxygen pump 1 through a metal wire, and the negative electrode of the constant voltage source 8 is connected to the second porous electrode 5 of the ceramic oxygen pump 1 through a metal wire, and the first porous electrode 4, the first electrolyte layer 6, the second porous electrode 5, the constant voltage source 8, and the ammeter 9 form a loop.
[0020] The ceramic material having oxygen ion conductivity is yttria-stabilized zirconium oxide co-doped with strontium and magnesium and gallium and lanthanum La. 1- x Sr x Ga 1-y Mg y O 3−d , where 0 <x<1,0<y<1,0<δ<1。
[0021] The thickness of the first electrolyte layer 6 and the second electrolyte layer 2 is 100 micrometers, and the thickness of the first porous electrode 4 and the second porous electrode 5 is 100 micrometers.
[0022] The height of the chamber 7 is 500 microns, the thickness of the sealing member 3 is 500 microns, and the thickness of the sealing member 3 is 500 microns.
[0023] The metal wire is a silver wire, and the output voltage of the constant voltage source 8 is 0.2V.
[0024] The output voltage of the above constant voltage source 8 is 0.1V The ceramic oxygen pump 1 is operated at 550°C.
[0025] Embodiment 2: A gas tightness detection device for a solid oxide battery, comprising: a ceramic oxygen pump 1 located at the top, a second electrolyte layer 2 located at the bottom, and a seal 3 located between the ceramic oxygen pump 1 and the second electrolyte layer 2, wherein the ceramic oxygen pump 1 is composed of a first porous electrode 4, a first electrolyte layer 6, and a second porous electrode 5 stacked in sequence, wherein the seal 3, the first electrolyte layer 6, and the second electrolyte layer 2 are arranged to form a chamber 7, and the second porous electrode 5 is located in the chamber 7; The first electrolyte layer 6 and the second electrolyte layer 2 are both ceramic materials with oxygen ion conductivity, the first porous electrode 4 and the second porous electrode 5 are electronically conductive materials or oxygen ion-electron mixed conductive materials, and the oxygen ion-electron mixed conductive materials are La 0.8 Sr 0.2 MnO 3-d , which is more conducive to the occurrence of oxygen reduction process on the oxygen pump electrode; The thickness of the first electrolyte layer 6 and the second electrolyte layer 2 is 10-1000 microns, the thickness of the first porous electrode 4 and the second porous electrode 5 is 10-1000 microns, the height of the chamber 7 is 50-2000 microns, and the thickness of the sealing member 3 is 50-2000 microns; It also includes: a constant voltage source 8 and an ammeter 9, wherein the positive electrode of the constant voltage source 8 is connected to the positive electrode of the ammeter 9, the negative electrode of the ammeter 9 is connected to the first porous electrode 4 of the ceramic oxygen pump 1 through a metal wire, and the negative electrode of the constant voltage source 8 is connected to the second porous electrode 5 of the ceramic oxygen pump 1 through a metal wire, and the first porous electrode 4, the first electrolyte layer 6, the second porous electrode 5, the constant voltage source 8, and the ammeter 9 form a loop.
[0026] The ceramic material having oxygen ion conductivity is strontium and magnesium co-doped with gallium and lanthanum La. 1-x Sr x Ga 1-y Mg y O 3−d , where 0 <x<1,0<y<1,0<δ<1。
[0027] The thickness of the first electrolyte layer 6 and the second electrolyte layer 2 is 150 micrometers, and the thickness of the first porous electrode 4 and the second porous electrode 5 is 150 micrometers.
[0028] The height of the chamber 7 is 300 microns, the thickness of the sealing member 3 is 300 microns, and the thickness of the sealing member 3 is 300 microns.
[0029] The metal wire is a platinum wire, and the output voltage of the constant voltage source 8 is 0.15V.
[0030] The ceramic oxygen pump 1 operates at 600°C.
[0031] The output voltage of the above-mentioned constant voltage source 8 is 0.3V.
[0032] As attached Figure 2 As shown in Figures (a) and (b), the airtightness test results of the package with seal 200 at 800°C and 0 and 0.23 kPa load pressures. A constant voltage of 0.3V is applied to both ends of the ceramic oxygen pump. Due to the leakage inside and outside the chamber, the pumped oxygen and the oxygen diffused into the cavity are balanced. After stabilization, it can be observed that a constant current platform value of 0.595mA is generated, reaching the milliampere level. The larger the current value, the higher the leakage rate and the worse the sealing effect. Combining Faraday's law of electrolysis and the electrode reaction equation, 0.595mA corresponds to a leakage amount of 3.0×10 -3 ml 3 ·min -1 cm -1 .
[0033] After applying a pressure of 0.23 kPa, since the seal 200 is subjected to a certain pressure, the bonding between the flowing glass and the adjacent components at this temperature is strengthened, the bonding interface is flat and has no obvious defects, the external oxygen cannot diffuse into the cavity, and the number of oxygen ion migration is extremely small. Therefore, when stable, the current platform of the constant potential polarization is extremely low, which is about 10 lower than the limiting current value of the sealing without load pressure at the same temperature. 4 The current is only 50nA, which is in the nanoampere level. -7 ml 3 ·min -1 cm -1 This shows that the sealing member 200 has excellent sealing ability under the temperature, pressure and pressure. Therefore, based on this method, the airtightness of the sealing member sealing the solid oxide battery can be quantitatively detected.
[0034] When the above-mentioned solid oxide battery airtightness detection device is used, the steady-state current value displayed by its ammeter directly reflects the gas leakage rate of the seal. The lower the steady-state current value, the higher the airtightness of the seal. Through the constant potential polarization method, this device can accurately detect the airtightness of the solid oxide battery stack seal in situ, and has the advantages of low cost and easy operation.
[0035] In addition, it uses the oxygen reduction reaction occurring on the electrodes of the oxygen pump battery at high temperature to pump out the oxygen in the sealed chamber and the oxygen leaking into the sealed chamber from the outside to reach the reaction kinetic equilibrium state, and combines with the electrochemical workstation to monitor the steady-state current generated by the reaction, and the size of this steady-state current reflects the degree of leakage of the seal. The leakage value can be calculated by combining Faraday's law of electrolysis and the current size detected by the electrochemical workstation. Using this method and device, it is possible to achieve quantitative characterization of the leakage rate of solid oxide batteries at different temperatures and pressures. For example, at a high temperature of 800°C and a loading pressure of 0.23kPa, the airtightness test results of the ceramic oxygen pump device packaged with a seal are: the current platform of the constant potential polarization is extremely low, the steady-state current size is only 50nA, and the current order of magnitude is nanoampere level. Based on Faraday's law of electrolysis and the electrode reaction equation, it can be calculated that the leakage corresponding to this current is 2.6×10 -7 ml 3 ·min -1 cm -1 , which is lower than the standard value of 0.04 ml for sealing material leakage specified by the US Department of Energy SECA program 3 ·min -1 cm -1 , indicating that the seal 200 has excellent sealing ability under the temperature and pressure. And the time to reach the oxygen pump current platform is short, showing fast and efficient detection ability. Therefore, based on this method, the sealing of the solid oxide battery during operation can be quantitatively detected.
[0036] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A gas tightness detection device for a solid oxide battery, characterized in that: include: A ceramic oxygen pump (1) located at the top, a second electrolyte layer (2) located at the bottom, and a sealing member (3) located between the ceramic oxygen pump (1) and the second electrolyte layer (2), wherein the ceramic oxygen pump (1) is composed of a first porous electrode (4), a first electrolyte layer (6), and a second porous electrode (5) stacked in sequence, the sealing member (3) and the first electrolyte layer (6) and the second electrolyte layer (2) enclose a chamber (7), and the second porous electrode (5) is located in the chamber (7); The first electrolyte layer (6) and the second electrolyte layer (2) are both ceramic materials with oxygen ion conductivity, the first porous electrode (4) and the second porous electrode (5) are electronically conductive materials or oxygen ion-electron mixed conductive materials, and the oxygen ion-electron mixed conductive materials are La 0.8 Sr 0.2 MnO 3-d ; The thickness of the first electrolyte layer (6) and the second electrolyte layer (2) is 10 to 1000 micrometers, the thickness of the first porous electrode (4) and the second porous electrode (5) is 10 to 1000 micrometers, the height of the chamber (7) is 50 to 2000 micrometers, and the thickness of the sealing member (3) is 50 to 2000 micrometers; The invention also comprises: a constant voltage source (8) and an ammeter (9), wherein the positive electrode of the constant voltage source (8) is connected to the positive electrode of the ammeter (9), the negative electrode of the ammeter (9) is connected to the first porous electrode (4) of the ceramic oxygen pump (1) via a metal wire, the negative electrode of the constant voltage source (8) is connected to the second porous electrode (5) of the ceramic oxygen pump (1) via a metal wire, and the first porous electrode (4), the first electrolyte layer (6), the second porous electrode (5), the constant voltage source (8), and the ammeter (9) form a loop.
2. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The ceramic material having oxygen ion conductivity is yttria-stabilized zirconia (Zr 1-x Y x O 2−d )、 Scandium oxide stabilized zirconia (Zr 1- x Sc x O 2−d ), samarium oxide doped cerium oxide (Ce 1-x Sm x O 2−d ), gadolinium oxide doped cerium oxide (Ce 1-x G x O 2−d ), SrMg co-doped Ga and Lanthanum (La 1-x Sr x Ga 1-y Mg y O 3−d ), erbium-stabilized bismuth oxide (Er x Bi 2-x O 3−d ), doped barium zirconate (BaZr 1-x Y x O 3−d ) or doped with barium cerate (BaCe 1-x Y x O 3−d ), where 0 <x<1,0<y<1,0<δ<1。 3. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The thickness of the first electrolyte layer (6) and the second electrolyte layer (2) is 20 to 600 micrometers.
4. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The thickness of the first porous electrode (4) and the second porous electrode (5) is 20 to 500 micrometers.
5. The airtightness detection device for solid oxide battery according to claim 1, characterized in that: The height of the chamber (7) is 200-1000 microns.
6. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The thickness of the sealing element (3) is 200-1000 microns.
7. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The thickness of the sealing element (3) is 200-1000 microns.
8. The airtightness detection device for solid oxide battery according to claim 1, characterized in that: The metal wire is a silver wire or a platinum wire.
9. The airtightness detection device for a solid oxide battery according to claim 1, characterized in that: The output voltage of the constant voltage source (8) is 0.1-0.3 V.
10. The airtightness detection device for solid oxide battery according to claim 1, characterized in that: The ceramic oxygen pump (1) operates at 500-850°C.
Citation Information
Patent Citations
Metal-supported solid oxide fuel cell and preparation method thereof
CN103872366A
Solid oxide electrolyte cell comprising electrolytic air
CN116093389A
Method for manufacturing unit cell of metal-supported solid oxide fuel cell
KR1020140092749A
Solid oxide fuel cell having a dense barrier layer
WO2014210494A1